Digitalization of Legal Transformation on Judicial Review in the Constitutional Court - Setiawan, Heru; Ketut Rachmi Handayani , I Gusti Ayu; Hamzah, M. Guntur; Tegnan , Hilaire (Lembaga Contrarius Indonesia, 2024)
Efficient, affordable, and uncomplicated justice poses a complex dilemma within the Indonesian judicial system. However, applying technological advancements to assessing legal regulations can resolve this issue. This research aims to examine the necessity and implementation of digitalization in the Constitutional Court's judicial review process. This research utilized a normative legal approach, characterized by its prescriptive and applied nature, to examine the development and implementation of digitalization in the justice systems of the European Union, the United States, and the United Kingdom through comparative studies. The research results show that: first, technology in the Constitutional Court's judicial review process can most effectively promote openness and clarity in the decision-making procedure. However, there remain several areas in which the Constitutional Court must further refine itself to attain digital status, as inconsistencies persist in its practical rulings. Consequently, the Constitutional Court must increase the rate of digital transformation in its judicial review operations. Second, numerous other nations, including the European Union, the United Kingdom, and the United States, have observed the implementation of technological advancements, leading to enhanced transparency and accessibility in their justice systems. Thirdly, to overcome the challenges above, we must apply the fundamental principles of good judicial governance, procedural law at the Constitutional Court, the paperless principle, and the contactless service principle when developing digital transformation for future judicial review at the Court. This will enable us to achieve transparency and accessibility in the Constitutional Court's judicial system.